Special review series on 3D organotypic culture models: Introduction and historical perspective - Hayden, Patrick J.; Harbell, John W. (In vitro cellular & developmental biology. Animal, 2021)
Three dimensional (3D) organ-like (organotypic) culture models are a rapidly advancing area of in vitro biological science. In contrast to monolayer cell culture methods which were developed to achieve proliferation of animal cells in the beginning of in vitro biology, the advancements in 3D culture methods are designed to promote cellular differentiation, and to achieve in vivolike 3D structure and organotypic functions. This project was conceived through the Society for In Vitro Biology to draw on the expertise of individual scientists with special expertise in organotypic cultures of selected tissues or associated interrogation methods to prepare individual-focused reviews in this series. This introductory manuscript will review the early achievements of animal cell culture in monolayer culture and the limitations ofthat approach to reproduce functioning organ systems. Among these are the nature and 3D architecture of the substrate on which or in which the cells are grown, physical and mechanical clues from the substrate, cell-cell interactions, and defined biochemical factors that trigger the induction of the 3D organotypic differentiation. The organoid culture requires a source of cells with proliferative capacity (ranging from tissue-derived stem or immortalized cells to the iPSC cultures), a suitable substrate or matrix with the mechanical and stimulatory properties appropriate for the organotypic construct and the necessary stimulation of the culture to drive differentiation of the cell population to form the functioning organotypic construct. Details for each type of organotypic construct will be provided in the following papers.